2008
DOI: 10.1038/nnano.2008.65
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-directed assembly of lines of 1,5-dichloropentane on silicon substrates by displacement of surface charge

Abstract: One-dimensional nanostructures at silicon surfaces have potential applications in nanoscale devices. Here we propose a mechanism of dipole-directed assembly for the growth of lines of physisorbed dipolar molecules. The adsorbate chosen was a halide, in preparation for the patterned imprinting of halogen atoms. Using scanning tunnelling microscopy, physisorbed 1,5-dichloropentane on Si(100)-2x1 was shown to self-assemble at room temperature into molecular lines that grew predominantly perpendicular to the Si-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…Surface buckling similar to the features marked "b" in Fig 1 was previously observed for 1,5-dichloropentane and also for pairs of 1-fluoropentane molecules (13,14). Exhaustive calculations showed that the buckling arose because of the asymmetry of these molecular pairs, which caused a buildup of charge and hence brightness at a silicon dimer located to one side of the adsorption site (13,14).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Surface buckling similar to the features marked "b" in Fig 1 was previously observed for 1,5-dichloropentane and also for pairs of 1-fluoropentane molecules (13,14). Exhaustive calculations showed that the buckling arose because of the asymmetry of these molecular pairs, which caused a buildup of charge and hence brightness at a silicon dimer located to one side of the adsorption site (13,14).…”
Section: Resultssupporting
confidence: 76%
“…The adsorption product that we image by STM consists, however, of stable CP pairs. In previous work (13,14) such stabilization of pairs was shown by theory to be due to charge-transfer in the surface. The rate of CP pair formation and subsequent line formation depends quadratically on the concentration of mobile CP (ad), whereas the competing rate of desorption back to the gas phase depends linearly on this quantity.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In some cases, these interactions were shown to dominate over forces resulting from chemical bonds between the molecules. Various examples can be found in published studies of organics under ambient atmospheric conditions, 1 at the liquid-solid interface 2 and under ultrahigh vacuum conditions, [3][4][5][6][7][8] with the molecular dipole aligned perpendicular to the surface 9 or within the surface plane, 3,4 and for various molecule sizes ranging from small molecules such as quinonoid zwitterions 3 and styrenes 4 to larger ones such as anthracene. 10 In reviewing those reported assemblies of dipolar molecules, it becomes evident that most of them do a) Electronic mail: ezurek@buffalo.edu b) Electronic mail: aenders2@unl.edu not correspond to a configuration of lowest electrostatic energy.…”
Section: Introductionmentioning
confidence: 99%